2013
DOI: 10.1097/aap.0b013e31828ea086
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroids

Abstract: Epidural steroid injections (ESIs) are the most widely utilized pain management procedure in the world, their use supported by more than 45 placebo-controlled studies and dozens of systematic reviews. Despite the extensive literature on the subject, there continues to be considerable controversy surrounding their safety and efficacy. The results of clinical trials and review articles are heavily influenced by specialty, with those done by interventional pain physicians more likely to yield positive findings. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(129 citation statements)
references
References 279 publications
1
125
0
3
Order By: Relevance
“…119 The evidence supporting other treatments for discogenic pain, including epidural and intradiscal injections, and thermal ablation, is weak and inconsistent. [120][121][122][123][124] Neuropathic pain Cervical disc herniation The annual incidence of cervical radiculopathy resulting from disc protrusion or degenerative spondylosis (or both) is estimated at 1-3.5 per 1000 person years, peaking in the sixth decade of life. A population based study reported a 0.055% incidence of radicular pain secondary to a cervical herniated disc, although estimates based on patients seeking medical attention underestimate incidence.…”
Section: Myofascial Painmentioning
confidence: 99%
See 2 more Smart Citations
“…119 The evidence supporting other treatments for discogenic pain, including epidural and intradiscal injections, and thermal ablation, is weak and inconsistent. [120][121][122][123][124] Neuropathic pain Cervical disc herniation The annual incidence of cervical radiculopathy resulting from disc protrusion or degenerative spondylosis (or both) is estimated at 1-3.5 per 1000 person years, peaking in the sixth decade of life. A population based study reported a 0.055% incidence of radicular pain secondary to a cervical herniated disc, although estimates based on patients seeking medical attention underestimate incidence.…”
Section: Myofascial Painmentioning
confidence: 99%
“…136 In both the lumbar and cervical regions, it is widely acknowledged that the benefits afforded by ESI for herniated discs are superior to those for spinal stenosis (table 2). 124 Exercise and integrative medicine Exercise is often touted as an effective treatment for chronic pain, although a recent Cochrane review found that the quality of evidence is low. 158 Exercise may be beneficial for neck pain by stimulating endorphin secretion, transforaminal approach reporting a negative outcome.…”
Section: Cervical Discogenic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options are largely uproven but include analgesic drugs of various categories including antiepileptics and antidepressants, injections of drug combinations into the spine and surgical techniques to remove the prolapsed disc [1] Recent evidence has suggested that the commonly used neuromodulator drug pregabalin may not have a strong benefit in the treatment of sciatica in the community [5]. Epidural steroid injections (ESI) are another treatment modality for sciatica and involve the administration of a mixture of local anaesthetic and steroid into the spine via one of three main routes; through the base of the spine (caudal epidural), through the back of the spine (inter-laminar) or through the nerve tunnel directly adjacent to the prolapsed disc (transforaminal epidural steroid injection (TFESI) [6]. Randomised controlled trials (RCTs) have looked at ESI for acute sciatica but these have not included comparisons between TFESI and inter-laminar ESI [710].…”
Section: Introductionmentioning
confidence: 99%
“…Randomised controlled trials (RCTs) have looked at ESI for acute sciatica but these have not included comparisons between TFESI and inter-laminar ESI [710]. However, prospective and case control studies have compared these and demonstrated a superior efficacy of TFESI [69]. One recent study of TFESI ([9]; n  = 238) reported that 65% of injections were effective at follow-up greater than 6 months (based on patient-reported measures) suggesting that the administration of drug closer to the disc prolapse may improve efficacy when compared to other methods of administration.…”
Section: Introductionmentioning
confidence: 99%